2020
DOI: 10.1136/jitc-2020-000705
|View full text |Cite
|
Sign up to set email alerts
|

SITC cancer immunotherapy resource document: a compass in the land of biomarker discovery

Abstract: Since the publication of the Society for Immunotherapy of Cancer’s (SITC) original cancer immunotherapy biomarkers resource document, there have been remarkable breakthroughs in cancer immunotherapy, in particular the development and approval of immune checkpoint inhibitors, engineered cellular therapies, and tumor vaccines to unleash antitumor immune activity. The most notable feature of these breakthroughs is the achievement of durable clinical responses in some patients, enabling long-term survival. These d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 563 publications
(336 reference statements)
0
20
0
Order By: Relevance
“…Recently, an increasing number of studies have demonstrated that TMB and immune cell infiltration played a vital role in immunotherapy response across multiple cancer types ( 48 , 49 ). Previous studies showed that blood TMB can be used as a predictive biomarker in patients with non-small cell lung cancer and platinum-resistant recurrent ovarian cancer ( 50 , 51 ). In addition, some studies have found there was a significant negative correlation between TMB values and prognosis prediction performances ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, an increasing number of studies have demonstrated that TMB and immune cell infiltration played a vital role in immunotherapy response across multiple cancer types ( 48 , 49 ). Previous studies showed that blood TMB can be used as a predictive biomarker in patients with non-small cell lung cancer and platinum-resistant recurrent ovarian cancer ( 50 , 51 ). In addition, some studies have found there was a significant negative correlation between TMB values and prognosis prediction performances ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, as physicians and scientists in the field of pediatric AML, we recognize the urgent need to initiate major immune characterization efforts. Meanwhile, the Society for Immunotherapy of Cancer's (SITC) has published a resource document on the use of immune profiling for different purposes [97]. In this resource document, the authors describe the discovery of biomarkers that are predictive of both response to immunotherapy and immune-related adverse effects.…”
Section: The Way Forward In Pediatric Aml: the Need For Immune Profilingmentioning
confidence: 99%
“…Although collectively ICIs have a response rate of 30–40% ( 6 ), a majority of patients lack satisfactory clinical efficacies owing to the complex mechanisms underlying tumor immunity ( 7 ). Furthermore, several reported genomic and immune biomarkers indicate that the therapeutic effects are not targeted and there is an inevitable bias whilst evaluating the treatment efficacies ( 8 ). Thus, it is challenging but necessary to identify a better predictor to evaluate the clinical outcomes accurately before prescribing ICI treatment.…”
Section: Introductionmentioning
confidence: 99%